The Intellectual Life of "Alzimma People" in the Land of the Kurds (447-656h / 1055-1258) - Ismail, First M.; Saadoun, Bashar (Humanities Journal of University of Zakho, 2017)
This research deals with the intellectual life of the people of "Alzimma People" in the country of the Kurds through their contribution to the study of mental and Transport sciences, mental sciences include: medicine, pharmacy, mathematics, engineering, astronomy, philosophy and other sciences. Transport sciences include: language, grammar, literature, history, geography and the arts. Each of the followers of "Alzimma People" of the Jews, Christians and Sabians played a role in the development of some of these mentioned sciences according to their importance to them, in other words, as required by their religious, social, cultural and economic conditions, and in accordance with their political situation in the country of the Kurds in the Abbasid era.